The Qur’an, the prophet’s life, and the Abbasid Caliphate: Insights from social psychology - Fontaine, Rodrigue Ancelot Harvey (2019)
This study attempts to use theories from social psychology to build a narrative that allows to better understand the Qur’an, the life of the Prophet, and the highlights of the Abbasid caliphate. Specifically, Zimbardo contrasts the dispositional view and the situational view. The situational view is created in turn by the System – the institutions that exits within a society. Though many people read the Qur’an and the Prophet’s life through the lens of a dispositional view, the situational view offers us new insight. The dispositional view sees people as being either good or bad. The situational view sees the situation as being either good or bad. In a bad situation, good people can behave badly. In a good situation, bad people can behave well. The massive conversions towards the end of the life of the Prophet makes no sense using the dispositional view. It makes perfect sense using the situational view. The study addresses on three questions. First, does the situational view help us better understand the Qur’an, the life of the Prophet, and Islamic history? Second, does the situational view help Muslims better understand the Qur’an and the Sunnah? Third, should encouraging good and forbidding evil be seen through the light of strengthening political and social institutions?